2021
DOI: 10.1080/09638288.2021.1955304
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of participation, mental health, and mental health problems in adolescents with self-reported neurodevelopmental disorders

Abstract: Purpose: Having a neurodevelopmental disorder (NDD) increases the risk of mental health problems and lower participation. We investigated the trajectories of mental health problems and participation in adolescents with NDD and compared these with trajectories for peers without NDD. In addition, the relationship between participation, mental health (well-being), and mental health problems were investigated. Materials and methods: Data from a Swedish longitudinal survey study (LoRDIA) was used and adolescents wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Neurodevelopmental disorders—or congenital disorders of brain system development causing cognitive and behavioral impairments—have wide-ranging consequences for academic, social, and mental health outcomes. 1 , 2 These disorders—affecting ∼53 million children within the first 5 years of life (i.e. a prevalence of 12%) 3 —are the third-ranked form of child disability, after vision and hearing loss.…”
mentioning
confidence: 99%
“…Neurodevelopmental disorders—or congenital disorders of brain system development causing cognitive and behavioral impairments—have wide-ranging consequences for academic, social, and mental health outcomes. 1 , 2 These disorders—affecting ∼53 million children within the first 5 years of life (i.e. a prevalence of 12%) 3 —are the third-ranked form of child disability, after vision and hearing loss.…”
mentioning
confidence: 99%
“…If some children rarely become engaged in activities with other children or adults, objects, or symbols, on a regular basis over long periods of time, less proximal processes will occur, leading to a negative impact on child development (Bronfenbrenner and Morris, 2006;Merçon-Vargas et al, 2020). Children's health and well-being will probably also suffer as these outcomes are closely related to participation (e.g., Augustine et al, 2022). A recent Swedish longitudinal preschool study using cluster analysis (Gustafsson et al, 2021) showed that children displaying more extreme behavioral patterns (e.g., highly favorable or unfavorable) tend to display similar patterns over time, while children in clusters close to the mean tend to change patterns more often.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivity, for example, is a common coexisting problem for many children with disabilities, and some may exhibit hyperactive behaviour without having conduct or emotional problems [ 9 ]. In adolescents with neurodevelopmental disorders (NDD), hyperactivity seems to be more stable over time than conduct and emotional problems, and rather be related to the NDD [ 4 ]. Likewise, peer problems may be a consequence of difficulties inherent to a child’s disability, such as communication problems.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, peer problems may be a consequence of difficulties inherent to a child’s disability, such as communication problems. Peer problems may also be related to the behaviour of others, rather than an expression of mental health problems of the child [ 4 , 10 ]. Including hyperactivity and peer problems in studies of children with disabilities may therefore lead to an overestimation of the prevalence of mental health problems.…”
Section: Introductionmentioning
confidence: 99%